Understanding voice problems - Colton, Raymond H.; Casper, Janina K.; Leonard, Rebecca (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Understanding Voice Problems: A Physiological Perspective for Diagnosis and Treatment emphasizes the physiological perspective of voice disorders and the behavioral and emotional factors that can influence these changes. Readers will find a strong foundation in normal phonatory physiology and acoustics as well as pathophysiology arising from voice misuse, abuse, or neurological involvement. Coverage includes in-depth explorations of patient interviewing, history-taking, examination, and testing and discussions of pediatric and geriatric voice considerations. The book contains numerous illustrations, including full-color plates of vocal fold pathologies. A companion Website features nearly 30 video clips that demonstrate healthy, normally functioning larynges at work, plus larynges with various pathological problems"--Provided by publisher.
Machine generated contents note: Color plates precede page i Preface 1 Introduction and Overview 2 Differential Diagnosis of Voice Problems 3 Morphology of Vocal Fold Mucosa: Histology to Genomics 4 Phonotrauma: Its Effects on Phonatory Physiology 5 Voice Problems Associated With Nervous System Involvement 6 Voice Problems Associated With Organic Disease and Trauma 7 Voice Problems Associated With the Pediatric and the Geriatric Voice 8 The Voice History, Examination, and Testing 9 Surgical and Medical Management of Voice Disorders 10 Vocal Rehabilitation 11 Anatomy of the Vocal Fold Mechanism 12 Phonatory Physiology 13 Neuroanatomy of the Vocal Mechanism 14 Some Normative Data on the Voice Appendix: Forms Used in Voice Evaluation: Clinic and Laboratory References Figure and Table Credits Index .
Keywords: Audiology